Comparative effect of probiotic (Saccharomyces cerevisiae), prebiotic (Fructooligosaccharide) and their combination on some blood indices in young common carp (Cyprinus carpio L.): Nasreen M. Abdulrahman and Vian M. Ahmed - Abdulrahman, Nasreen M. (The Iraqi Journal of Veterinary Medicine, 2016)
This study was carried out to examine the effect of Fructooligosaccharide as a source of prebiotic, and commercial dry yeast (Saccharomyces cerevisiae) as a source of probiotic and their combination in different level as a source of synbiotic. The experiment was conducted in the fish laboratory of Animal Production Department, Faculty of Agricultural Sciences of Sulaimani University. The trials lasted for three months after 21 days of adapting period 120 common carp fingerlings with an average weight of 20 ±2 gm, were used to test the effect of different levels of the Fructooligosaccharide, yeast and their combination. In T1 fish were fed a diet with 2.5 gm/kg Fructooligosaccharide, in T2, fish were fed a diet 2.5 gm/kg yeast, T3 represents the third treatment, in which fish were fed on a diet 5 gm/kg Fructooligosaccharide. While, in T4 fish were fed a diet 5 gm/kg yeast, and T5 2.5 Fructooligosaccharide: 2.5 Yeast (gm/kg), T6 was 5 Fructooligosaccharide: 5 yeast (gm/kg), T7 2.5 Fructooligosaccharide: 5 Yeast gm/kg), while T8 5 Fructooligosaccharide, 2.5 (gm/kg) Yeast. Each treatment in three replicates in which five fingerlings common carp were stocked in plastic tanks, which fed the experimental diets twice daily. Blood parameters of tested fish showed significant differences in Red blood cell count (1012 cells/l) in T5 and T7 by 1.235 and 1.260, respectively. Hemoglobin (g/dl) data were 117.000 in the fifth treatment. The mean corpuscular hemoglobin (pg/cell) was 121.400 in T2, 137.850 in T3, 121.050 in T4, and 135.300 in T6; mean corpuscular hemoglobin concentration (g/l) was 924.000, in the seventh treatment, mean corpuscular volume were (fL) 232.500 and 233.050 in T4 and T8 respectively. There were different effects of the treatment in the studied blood parameters in which the level of 2.5 g/kg in both Fructooligosaccharide and dry yeast affect significantly the Red blood cell, White blood cell and Hemoglobin.